Development of a scale to measure teaching practices for engaging Mexican families in education - Alberto Valdés Cuervo; Ernesto Alonso Carlos Martínez; Maricela Urías Murrieta; Teodoro Rafael Wendlandt Amezaga (Arizona State University, 2016)
Psychometric properties of an instrument were established to measure, from the perspective of parents, practices used by teachers to involve parents in the education of children. 640 parents of students from 11 public elementary schools from a state in northwestern Mexico participated in the study, 390 (60.9%) mothers and 250 (39.1%) fathers. The results suggest a good fit with the internal structure measurement model of the construct comprising the dimensions of learning support, school communication and collaboration with the school and community (c2= 52.99, p= .011; c2/gl= 1.656; SRMR= .05; GFI= .95; CFI= .97; RMSEA= .043 IC 90 [.032-.066]). This scale presents evidence of concurrent validity in explaining a significant portion of the frequency of parental involvement in education (F= 63.74, p .001; R2= .23). It is concluded that the instrument can be used in the analysis of the teaching practices of primary education to encourage participation of parents in the education of children in Mexico.